Retinol Binding Protein 4 Concentrations Relate to Enhanced Atherosclerosis in Obese Patients with Rheumatoid Arthritis - Dessein, Patrick H. (Public Library of Science, 2014)
BACKGROUND: Retinol binding protein 4 (RBP) enhances metabolic risk and atherogenesis. Whether RBP4 contributes to cardiovascular risk in rheumatoid arthritis (RA) is unknown. METHODS: We assessed RBP4 concentrations and those of endothelial activation molecules including E-selectin, vascular cell adhesion molecule-1, intercellular adhesion molecule-1 and monocyte chemoattractant protein-1 by ELISA, and the common carotid artery intima-media thickness (cIMT) and carotid artery plaque by ultrasound in 217 (112 black and 105 white) patients with RA. Relationships were identified in potential confounder and mediator adjusted mixed regression models. RESULTS: RBP4 concentrations were associated with systolic and mean blood pressure, and those of glucose and E-selectin (partial R = −0.207 (p = 0.003), −0.195 (p = 0.006), −0.155 (p = 0.03) and −0.191 (p = 0.007), respectively in all patients); these RBP4-cardiovascular risk relations were mostly reproduced in patients with but not without adverse traditional or non-traditional cardiovascular risk profiles. RBP4 concentrations were not associated with atherosclerosis in all patients, but related independently to cIMT (partial R = 0.297, p = 0.03) and plaque (OR (95%CI) = 2.95 (1.31–6.68), p = 0.008) in those with generalized obesity, as well as with plaque in those with abdominal obesity (OR (95%CI) = 1.95 (1.12–3.42), p = 0.01). CONCLUSION: In the present study, RBP4 concentrations were inversely associated with metabolic risk and endothelial activation in RA. This requires further investigation. RBP4 concentrations were related to enhanced atherosclerosis in patients with generalized or/and abdominal obesity.